Graphene nanoplatelets enhanced myo-inositol for solar thermal energy storage. (June 2017) - Singh, D.K.; Suresh, S.; Singh, H.
Graphical abstract: Highlights: MI-GNN were investigated physically and chemically. Good thermal stability was shown by MI-GNN. MI interacted with GNN only physically. Mass loss of MI-GNN was less after thermal cycling. Abstract: Thermal behavior of nanocomposite phase change materials, Myo-inostol (MI) (a sugar alcohol) added with graphene nanoplatelets (GNN) as a solar thermal energy storage system, for use in the temperature range of 100–260 °C was studied. GNN is added to MI with mass fraction of 1.0, 2.0 and 3.0 wt%. Thermal and chemical stability of MI and MI-GNN were investigated before and after 50 thermal cycles. Results showed that the dispersion of GNN into pure MI was effective, no crystal change and chemical reaction had taken place between GNN and MI before and after thermal cycling, only physical interaction between them had taken place. GNN particles were dispersed throughout the MI with small aggregates. The heat of fusion was found to decrease by 14.13%, 15.06% and 17.63% and heat of solidification by 13.02%, 23.12% and 29.68% for MI-GNN with 1.0, 2.0 and 3.0 wt% of GNN added to MI respectively.